INFLUENCE OF EXPOSURE ON PUBLIC ACCEPTANCE TOWARDS PHYSICAL ACTIVITY INVOLVEMENT OF PEOPLE WITH DISABILITIES (PWD): EXPLORING THE MEDIATING ROLE OF ATTITUDE USING SEM APPROACH - Fatt, Ong; Rasid, Aida (PEOPLE: International Journal of Social Sciences, 2017)
Societal acceptance towards disability can have a distressing impact upon the self-confidence and self-image of people with disabilities (PWD), which can discourage the involvement of person with disabilities in physical activity. This study aims to examine the causal relationships of exposure and attitude components on public acceptance towards PWD involvement in physical activity. A convenience sampling technique was utilized to collect data from the public (n=444), at four urban Public Recreation Park in Klang Valley, Malaysia. Structural equation modeling analysis was utilized to assess the hypothesized conceptual model, and examines the relationship among the constructs. Attitude (β=.473, p<.01) displays stronger influence on public acceptance compared to exposure (β=.204, p<.01). The findings revealed the partial mediating role of attitude in the relationship between exposure and public acceptance towards PWD involvement in physical activity. The findings suggest the need for public to have more exposure (experience, knowledge, contact) with the disabled community, which will cultivate positive attitude and hence improve the acceptance towards PWD involvement in physical activity. Future study can include meaningful assessment of other different factors, including their moderating effects. Implications of the result for future practice and directions of research were discussed.